Pelatihan penulisan artikel jurnal ilmiah bagi guru di MA Ma’arif NU Sains AL-Quran Sumbang - Asfi Aniuranti; Nur’aini Muhassanah (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2022)
Scientific publication is an activity that every academician, including teachers, should carry out. Publication activities can take various forms. One form of scientific publication is the publication of articles in scientific journals. Unfortunately, the publication of articles in partner schools, namely MA Ma'arif NU Science Al-Quran Contributes, still needs to be higher. Only 9.09% of teachers have experience writing articles; the rest, or as many as 90.91% of teachers, still need to carry out article publication activities. Therefore, training activities for writing scientific journal articles are needed. Article writing training activities are carried out offline and online. The series of activities consisted of providing theory related to scientific journal articles, independent practice, and writing assistance twice. The results of the activity show that there is a slight increase in the number of teachers who can compile articles. There, 27.27% of teachers have been able to compile complete articles. There are also 72.72% of teachers who have been able to access the Open Journal System (OJS) and are able to create accounts on journals. The results of the questionnaire also showed a positive response from the teacher. The "agree" option has the highest percentage across all items in the questionnaire. The results of the questionnaire show several important conclusions: 1) The teacher feels that the whole series of training activities is helpful; 2) Writing scientific journal articles is essential; 3) Teachers think that the publication process through OJS is easy to understand. Overall, the training activities have improved teachers' abilities in compiling articles and accessing OJS, and the training activities received positive responses.